Pengembangan E-Module Perancangan Roda Gigi Berbasis Project-Based Learning: Development of a Gear Design E-Module Based on Project-Based Learning - Muhammad Ali Ridho; Mochammad Amri Santosa (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This research was a development study aimed at producing a project-based learning (PjBL) e-module on gear material for the course Dynamic Machine Elements and Basic CAD/CAM. The method used was Research and Development (R&D) with the Holistic 4D model (Define, Design, Develop, Deploy). The study was conducted during the even semester of the 2024/2025 academic year. The research subjects were students of the Mechanical Engineering Education Study Program at Sriwijaya University. The research instruments consisted of expert validation questionnaires and student practicality questionnaires. The results showed that the validation of the material and media by validators indicated that the gear material e-module based on project-based learning achieved a material validation score of 88.57% and a media validation score of 90%, both of which fell into the “Very Valid” category. Based on the small group trial involving 28 students, the e-module was also found to be highly practical, with a practicality score of 64.10 and a percentage of 91.51%. These results were based on three assessment indicators: usefulness, user satisfaction, and ease of use, all of which were categorized as “Very Practical.” Therefore, it was concluded that the developed project-based learning e-module on gear material was categorized as very valid and practical for use in the student learning process.